A Sharper Picture of the Moon's Bombardment History From Gravity Data. Issue 9 (10th September 2018) - Nimmo, F.
Abstract: Some large impact basins on the Moon are covered with younger basalts, making it hard to determine their age by crater counting. Evans et al. (2018, https://doi.org/10.1029/2017JE005421 ) use Gravity Recovery and Interior Laboratory gravity data to identify buried craters larger than 90 km and construct a relative chronology for the impact basins. This relative chronology is broadly consistent with the degree to which the basins have relaxed: Older basins tend to be more relaxed. Pre‐Nectarian basins are likely saturated, so the roughly constant measured crater density does not require a brief formation interval. Some of the results of Evans et al. (2018) are at odds with other determinations; for example, they suggest that Imbrium could be older than Crisium, and Serenitatis as young as Imbrium. Plain Language Summary: To tell the age of an impact basin on the Moon, you count the number of craters. But some basins are flooded by later lavas, making crater counting difficult. Evans et al. (2018) identify buried craters by looking for small changes in the Moon's gravity. This allows them to decide how old each impact basin is. The older basins are also generally shallower. This is because the older basins formed when the Moon was hotter and the lunar rocks were able to flow and partly fill the basin in. Key Points: Evans et al. (2018) use gravity data to identify buried craters within large basins They reinterpret the relative ages of lunar basins using these observations The relative ages correlate quite well with the degree of basin relaxation